Enantioselective Sulfonation of Enones with Sulfinates by Thiourea/Tertiary-Amine Catalysis - Wang, Si-fan; Yan, Ming; Shi, Jin-yi; Li, Guang-xun; Zhao, Jin-zhong (Synlett, 2023)
Chiral γ-keto sulfones are significant structures in both organic synthesis and pharmaceutical chemistry. Although there are many choices for obtaining racemic forms, only a few enantioselective methods have been reported. We have developed a simple way for obtaining chiral γ-keto sulfones in moderate yields and moderate enantiomeric ratios. Readily available sulfinates were directly used as substrates that could be converted into sulfinic acids by treatment with boric acid. The bifunctional catalyst forms a chiral ion pair with the sulfinic acid and controls the enantioselectivity of the sulfonation through hydrogen bonding.
Keywords: keto sulfones; organocatalysis; thioureas; tertiary amines; sulfonation